STUDY ON THE EFFECT OF POLYSACCHARIDES FROM SOLANUM NIGRUM LINNE ON CELLULAR IMMUNE FUNCTION IN TUMOUR-BEARING MICE - Chen, Hai; Qi, Xiaodong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
We investigated the anti-tumour effect of polysaccharides from Solanum nigrum Linne, and its relationship with the immune function of tumour-bearing organisms, MTT assay was used to observe the effect of different doses of polysaccharides from Solanum nigrum Linne on proliferation of lymphocytes in tumour-bearing mice. ELISA assay was also used to detect the levels of IL-2 in mice, and a laser scanning confocal microscope was used to detect the effect of polysaccharides from Solanum nigrum Linne on intralymphocytic free calcium ion concentration in tumour-bearing mice. Different doses of polysaccharides from Solanum nigrum Linne significantly inhibited the growth of mouse H22 solid tumours, improved the survival time of tumour-bearing mice, increased the proliferation of lymphocytes, elevated the levels of IL-2, and increased the concentration of calcium ions in the lymphocytes. Polysaccharides from Solanum nigrum Linne have certain anti-tumour effect, which is related with the cellular immune function that regulates the body.